The application of diamines for amine transaminase mediated biotransformations - Gomm, Andrew (2019)
Section 1 gives an overview of the importance of chiral amines, along with a short summary of important non-enzymatic catalytic methods for chiral amine synthesis. A more detailed overview of biocatalytic methods for chiral amine synthesis is provided, with a focus given to amine transaminases. Based upon this summary the aims of this PhD thesis are distilled in section 2.